A note on (I, J)-e-continuous and (I, J)-e ∗ -continuous functions (2023)
In this paper the notions of I-e-open set and I-e∗-open set are introduced and used to define a large number of modifications of the concept of continuous function, such as (I, J)-e-continuous functions, (I, J)-e∗-continuous functions, contra (I, J)-e-continuous functions, contra (I, J)-e∗-continuous functions, almost weakly (I, J)-e-continuous functions, almost weakly (I, J)-e∗-continuous functions, almost (I, J)-e-continuous functions, almost (I, J)-e∗ -continuous functions, almost contra (I, J)-econtinuous functions and almost contra (I, J)-e∗-continuous functions. Also, several characterizations of these new classes of functions are given and finally relations between them are investigated.